2006
DOI: 10.1007/s11238-005-4750-2
|View full text |Cite
|
Sign up to set email alerts
|

The Ecological Rationality of Simple Group Heuristics: Effects of Group Member Strategies on Decision Accuracy

Abstract: The notion of ecological rationality implies that the accuracy of a decision strategy depends on features of the information environment in which it is tested. We demonstrate that the performance of a group may be strongly affected by the decision strategies used by its individual members and specify how this effect is moderated by environmental features. Specifically, in a set of simulation studies, we systematically compared four decision strategies used by the individual group members: two linear, compensat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Analytically, Reimer and Katsikopoulos showed that when the (average) recognition validity α is larger than the (average) knowledge validity β, then a group that recognizes fewer objects (movies) will perform better than a group that recognizes more. Judging from Reimer and Katsikopoulos' results, group members seem to grasp and trust the recognition heuristic and the wisdom encapsulated in partial ignorance (see Reimer & Hoffrage, 2006, for more on simple group heuristics).…”
Section: Social Decision Making In Games Against Naturementioning
confidence: 99%
“…Analytically, Reimer and Katsikopoulos showed that when the (average) recognition validity α is larger than the (average) knowledge validity β, then a group that recognizes fewer objects (movies) will perform better than a group that recognizes more. Judging from Reimer and Katsikopoulos' results, group members seem to grasp and trust the recognition heuristic and the wisdom encapsulated in partial ignorance (see Reimer & Hoffrage, 2006, for more on simple group heuristics).…”
Section: Social Decision Making In Games Against Naturementioning
confidence: 99%
“…This characteristic does not hold for all common-cue environments. It is possible to construct common-cue environments in which the best choice alternative can only be found on the basis of more complex decision strategies, such as weighted additive models (see, e.g., Reimer & Hoffrage, 2006). Thus, future studies may address whether the observed differences between unique-and common-cue environments can be generalized across information environments that demand more complex decision strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The weights used for the implementation of the compensatory WADD model were obtained by rescaling the validities presented on the screen into Goodman-Kruskal validities (i.e., weight = 2 × validity − 1) to control for chance (Reimer & Hoffrage, 2006). The movie pairs were selected such that a simple non-compensatory LEX strategy made opposite predictions to a WADD or EQW strategy (the latter two made similar predictions).…”
Section: Choice Taskmentioning
confidence: 99%